Entrepreneurship Based Education Management in Pesantren Jawahirul Hikmah Tumpuk Besuki Tulungagung - Imam Saerozi; Imam Junaris; Ahmad Nurcholis; Syaikhu Ihsan Hidayatullah (Ta'dib: Jurnal Pendidikan Islam, 2023)
The purpose of this study was to describe and analyze the strategy, implementation, and implications of entrepreneurial-based Islamic boarding school management in Pesantren Jawaahirul Hikmah Tumpuk, Besuki, Tulungagung. A qualitative study was conducted. The data were collected by interviewing 7 informants and observations. Data analysis was done logically and systematically following some steps including data reduction, data display, and conclusions. The results of the study showed that: First, the entrepreneurship education strategy used is students’ engagement in each stage of activity of entrepreneurship and designing meaningful learning. Second, the implementation of entrepreneurship education carried out by the Jawaahirul Hikmah Islamic boarding school in realizing institutional independence began with the implementation of the vision, mission and entrepreneurship education program as a guide for student creativity. Third, the implications of entrepreneurship education the pesantren were realized by subsidizing half of the students’ fee from the business profit.